Fitrah-Based education as an alternative paradigm for character development in early childhood education: a narrative review - Suprihatin, Riska Juniar (Panicgogy International Journal, 2024)
This study aims to analyze the concept of Fitrah-Based Education (FBE) as an alternative paradigm for character development in Early Childhood Education (ECE). This approach emphasizes the importance of exploration, experience, and play in fostering children's character in alignment with their natural fitrah. The research employs a narrative review method by examining and analyzing various literature sources related to the concepts, principles, and implementation of FBE in ECE. Data sources include scientific journals, books, and relevant educational policy documents. The analysis involves comparing different perspectives on FBE, identifying supporting factors and challenges in its implementation, and exploring the most effective learning models for character development based on fitrah. The findings indicate that FBE has significant potential in shaping children's character naturally and holistically. Exploration- and play-based learning enable children to develop moral, social, and emotional values in ways that align with their developmental stages. Furthermore, the active involvement of teachers and parents plays a crucial role in ensuring the success of this approach. Key supporting factors in implementing FBE include a deep understanding of the fitrah concept, flexible educational policies, and a conducive learning environment for children's development. Thus, FBE can serve as a more humanistic and developmentally appropriate character education approach in early childhood. Collaboration among educators, parents, and policymakers is essential to optimize the implementation of FBE within the ECE system, ensuring that children develop optimally according to their natural fitrah.